Equity Method Investments and Sell-Side Analysts' Information Environment - Lee, Sam (Sunghan); Pandit, Shailendra; Willis, Richard H. (The Accounting Review, 2013)
ABSTRACT: We study the joint effects of intercompany investing and reporting of equity method investments on the accuracy and dispersion of analysts' annual earnings-per-share (EPS) forecasts. We compare firm-year observations with and without equity method investments. We posit two non-mutually exclusive explanations for how equity method investments may affect analyst forecast properties. The Opacity Effect posits that the condensed equity method disclosures increase information asymmetry, increasing analysts' forecast errors and forecast dispersion. The Diversification Effect suggests that the diversification of the investor and its investee earnings streams enhances earnings predictability, decreasing analysts' forecast errors and forecast dispersion. Our findings are consistent with both effects operating in the analyst forecasting task. Additional analyses are consistent with the Opacity Effect dominating. This occurrence results, on net, in less accurate and more dispersed forecasts for firm-years with equity method investments. JEL Classifications: G14, M41